Comparative investigation of spectroelectrochemical and biosensor application of two isomeric thienylpyrrole derivatives. Issue 65 (16th July 2015) - Ayranci, Rukiye; Soganci, Tugba; Guzel, Merve; Demirkol, Dilek Odaci; Ak, Metin; Timur, Suna
<x xml:space="preserve">Abstract</x> In the present work, we performed a comparative investigation of spectroelectrochemical and biosensor application of two isomeric thienylpyrrole derivatives.